Hepatic hypertrophic osteoarthropathy and liver transplantation. Issue 5 (May 1994) - Pitt, P; Mowat, A; Williams, R; Hamilton, E
Abstract : OBJECTIVES–To document the variety of liver diseases and the clinical picture of hepatic hypertrophic osteoarthropathy (HOA) complicated by arthritis and to report the effects of successful liver transplantation on this disabling condition. METHODS–Seven patients with severe liver disease (two biliary atresia, two primary sclerosing cholangitis, one Wilson's disease, one primary biliary cirrhosis (PBC) and one alcoholic cirrhosis) complicated by radiologically proven hepatic HOA and suffering from arthritis are described. RESULTS–In four of the six patients who required hepatic transplantation for inadequate liver function successful grafting was achieved with complete clinical remission of the painful arthritis. This occurred three days to 18 months later. CONCLUSIONS–Hepatic HOA with arthritis occurs in a variety of liver diseases. Despite resistance of this arthritis to conventional therapies, successful liver transplantation was associated with complete clinical remission in four of the cases reported.